2015
DOI: 10.1371/journal.pone.0139165
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Biomarker and Co-Regulatory Motifs in Lung Adenocarcinoma Based on Differential Interactions

Abstract: Changes in intermolecular interactions (differential interactions) may influence the progression of cancer. Specific genes and their regulatory networks may be more closely associated with cancer when taking their transcriptional and post-transcriptional levels and dynamic and static interactions into account simultaneously. In this paper, a differential interaction analysis was performed to detect lung adenocarcinoma-related genes. Furthermore, a miRNA-TF (transcription factor) synergistic regulation network … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Methylenetetrahydrofolate dehydrogenase 2 (MTHFD2) has redox homeostasis and can be used in the treatment of lung cancer (Nishimura et al, 2019). NR3C1 is reported to be involved in the pathways related to the biological process of lung cancer, and as a gene marker has a significant correlation with the survival of LUAD (Zhao et al, 2015;Luo et al, 2018). Cathepsin L1, as a protein was encoded by the CTSL1 gene, could reduce the cellular matrix and proteolytic cascades which resulting to promote invasion or metastatic activity (Duffy, 1996;Turk et al, 2012).…”
Section: The Biological Significance Of the Selected Genes In Lung Camentioning
confidence: 99%
“…Methylenetetrahydrofolate dehydrogenase 2 (MTHFD2) has redox homeostasis and can be used in the treatment of lung cancer (Nishimura et al, 2019). NR3C1 is reported to be involved in the pathways related to the biological process of lung cancer, and as a gene marker has a significant correlation with the survival of LUAD (Zhao et al, 2015;Luo et al, 2018). Cathepsin L1, as a protein was encoded by the CTSL1 gene, could reduce the cellular matrix and proteolytic cascades which resulting to promote invasion or metastatic activity (Duffy, 1996;Turk et al, 2012).…”
Section: The Biological Significance Of the Selected Genes In Lung Camentioning
confidence: 99%
“…in the Dialogue of Reverse Engineering and Assessment of Methods (DREAM) competitions 11 and many more comparisons on smaller scale [12][13][14][15][16][17][18] . They have provided many biological insights, and have been particularly useful to elucidate mechanisms of pathogenicity in human diseases such as cancer 1,2,[19][20][21][22][23][24] . However, there is a disconnect between evaluation in often relatively simple systems (synthetic networks or GRNs in E. coli and yeast) and their application to much more complex mammalian systems.…”
Section: Introductionmentioning
confidence: 99%
“…Lung adenocarcinoma is a malignant cancer and a primary subtype of non-small cell lung cancer (NSCLC), with the greatest incidence and the worst prognosis worldwide (1). In the majority of cases the development of lung adenocarcinoma is a multifactor and multistage process, which is associated with numerous genes (2).…”
Section: Introductionmentioning
confidence: 99%
“…A previous study on the synergistic regulation of microRNAs (miRNAs) and TFs have identified a variety of significant motifs (15). In addition, a miRNA-TF synergistic regulation network has been constructed (2).…”
Section: Introductionmentioning
confidence: 99%